21st century guitar evolutions and augmentations - (Guitarist) McGrath, John.; (Guitarist) Perks, Rich. (New York Bloomsbury Academic, 2023)
examines the diverse physical manifestations of the guitar which have emerged in response to the needs of the modern performer and explores the creative possibilities these new forms afford"--
The well-tuned guitar / John Schneider -- Transforming the microtonal fingerboard : 'small' frets, LEGO and robots - Interview with Tolgahan Çoğulu / Richard Perks -- The expanding fretless guitarscape : practice and progress / Richard Perks -- Touching the apple without gloves - Interview with Cenk Erdoğan / Richard Perks -- Extended range instruments : Towards a new organology of the guitar / Tom Williams -- I should have just learned how to play the organ - Interview with Charlie Hunter / Richard Perks -- The transformed space of the Ligeti guitar / Katalin Koltai -- Grains, glitches and infinite space : guitar effects pedals, digitization and textural guitar aesthetics / Robert Strachan -- The sonic maelstrom - Interview with Nels Cline / John McGrath -- "Something seems wrong, should that be happening?" : avantfolk guitar and glitch aesthetics, a practice-based perspective / John McGrath -- "A field of reactivity" : Moog guitar and experimental systems - Interview with Bill Thompson / John McGrath -- The digital fretboard : remapping and relearning the guitar's pitch matrix with MIDI and Max/MSP / Milton Mermikides -- Augmented reality guitars : extended instruments and notation for a 21st century practice / Amy Brandon.
includes bibliographical references and index.
description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Electric guitar -- Performance; Guitar -- Performance; Guitarists -- Interviews; Guitar -- Construction -- History -- 21st century